Spontaneous Subdural Empyema: A Case Report - Dutta, Deep; Ahmed, Shameem; Borkotoky, Abhigyan (Asian Journal of Neurosurgery, 2023)
Subdural empyema is the collection of purulent material between the dura mater and arachnoid. Subdural empyema most often occurs due to the direct extension of local infection. But spontaneous subdural empyema is a rare entity. In literature, not many cases of spontaneous subdural empyema by Escherichia coli are reported. Here we report a case of spontaneous subdural empyema along with a review of literature who was previously treated on the suspicion of encephalitis with urinary tract infection and then brought to our hospital.
Keywords: E. coli; encephalitis; paranasal sinuses; purulent; subdural empyema